STUDY ON VIBRATION CHARACTERISTICS OF ROTOR SYSTEM WITH COUPLING FAULT OF DISC⁃SHAFT LOOSENESS AND RUBBING - TIAN DanYang; LI ZhiNong; ZHOU ShiJian; LI YunLong (Jixie qiangdu, 2024)
During the operation of the rotor system,parts may fall and loose,resulting in rubbing between the external object and the rotor shaft.To solve this problem,a finite element model of rotor systems with coupling fault was established by considering the case that disc⁃shaft loosening and rubbing occur simultaneously.Ansys was employed to simulate the rotor system.The influence of the looseness on the vibration characteristics of the rotor system was analyzed.Experiments were carried out to verify the simulation results.The results show that the time⁃domain waveform of the rotor system changes periodically,and the spectrogram mainly contains the first harmonic component.With the aggravation of the looseness,high frequency components gradually appear in the spectrum.The initial value of the speed difference of the disc⁃shaft in the start⁃up phase gradually increases with the aggravation of the loosening.The vibration amplitude of the disc center trajectory in the vertical direction also increases with the aggravation of the looseness,and the orbit shape becomes more complex.Due to the influence of the rubbing,the vibration in the vertical direction is obviously suppressed,and its amplitude is smaller than that in the horizontal direction.The research results have very important reference value for the study on dynamic characteristics of rotor systems with coupling faults.